Synthesis and structures of bora-amidinate lanthanide(III) complexes - Harder, Sjoerd (Dalton Transactions, 2010)
The use and coordination modes of the dianionic bora-amidinate ligand in lanthanide(iii) chemistry is explored. Synthetic routes to complexes of the type NBN-LnR (Ln = lanthanide, NBN = HB[N(2,6-iPr -phenyl)], R = an amide or benzylide group) have been developed. The reaction of NBN-H with (DMA) Sm (DMA = 2-MeN-benzyl) gave dark-red crystals of NBN-Sm(DMA) in 68% yield. The yttrium analogue, NBN-Y(DMA), was prepared similarly (yellow crystals, 58% yield). The reaction of NBN-Sm(DMA) with (MeSi)NH gave NBN-SmN(SiMe)·(THF) (yellow crystals, 54% yield). Crystal structure determinations of NBN-Sm(DMA) and NBN-Y(DMA) revealed dimeric complexes that are held together by Ln⋯DIPP interactions. The complex NBN-SmN(SiMe)·(THF) crystallized as a monomer. NMR investigations of [NBN-Y(DMA)] in benzene indicate that it is also dimeric in solution. The addition of THF resulted in its dissociation into monomeric units of NBN-Y(DMA)·(THF). © The Royal Society of Chemistry 2010.